Intelligent network control middleware platform. - Liu, Kenneth H. (IEEE Communications magazine)
As multivendor, multitechnology networks are deployed in a carrier's network, a network operator must integrate these networks to have a unified control platform to lower operational costs and deliver customer-specified QoS. An intelligent network control middleware framework for multivendor networks is described in this article. The architectural framework is designed to control and manage next generation network elements as well as legacy telecom networks. The layers within the framework include mediation, control plane, network resource management, and application programmable interfaces. An independent, distributed control plane aims at service interoperability and network scalability. An experimental study on circuit provisioning using the proposed middleware framework is conducted on Sun Lab servers. The middleware performance results are reported. Experimentation architecture and metrics can be extended to a performance benchmark upon which the control plane products can be evaluated.